2017
DOI: 10.1111/jocn.13385
|View full text |Cite
|
Sign up to set email alerts
|

Participatory design facilitates Person Centred Nursing in service improvement with older people: a secondary directed content analysis

Abstract: Aims and objectivesTo explore, using the example of a project working with older people in an outpatient setting in a large UK NHS Teaching hospital, how the constructs of Person Centred Nursing are reflected in interviews from participants in a Co‐design led service improvement project.BackgroundPerson Centred Care and Person Centred Nursing are recognised terms in healthcare. Co‐design (sometimes called participatory design) is an approach that seeks to involve all stakeholders in a creative process to deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…It also ensures that the focus remains on the end-user (24). These approaches have been successfully used in health service redesign (25)(26)(27), to promote self-management (for example the Intelligent Shoe in stroke rehabilitation (28,29)) and in MND (patient-education websites (30), and the Head-Up collar (31)).…”
Section: Introductionmentioning
confidence: 99%
“…It also ensures that the focus remains on the end-user (24). These approaches have been successfully used in health service redesign (25)(26)(27), to promote self-management (for example the Intelligent Shoe in stroke rehabilitation (28,29)) and in MND (patient-education websites (30), and the Head-Up collar (31)).…”
Section: Introductionmentioning
confidence: 99%
“…There are many models for delivering innovation, but, particularly in response to the drive for person-centred approaches (Berwick 2013), the approach offered by design is gathering support (Asch and Rosin 2015) whilst more evidence around participatory designs' ability to promote person-centred behaviour (Wolstenholme et al 2016) is reported.…”
mentioning
confidence: 99%
“…In nursing practice, Wolstenholme, Ross, Cobb, and Bowen (2017) provide such an example in an industrialized country, by describing the co-design of a service improvement project, where older people and other stakeholders were involved in the creative process. The authors found that the participatory or co-design practice inheres some of the underpinning philosophy of Person-Centred Nursing.…”
Section: Moving Forward In Nursing Education Through a Participatory mentioning
confidence: 99%